Museum Audio Descriptions vs. General Audio Guides: Describing or Interpreting Cultural Heritage? - Bartolini, Chiara (Journal of Audiovisual Translation, 2023)
The question of objectivity vs. subjectivity in audio description (AD) is still open and unresolved, even more so when considering less researched AD sub-genres, such as museum ADs. While sparse guidelines for describing artworks and cultural artefacts tend to favour neutrality, no clear consensus exists, and the limits of a factual style have already been highlighted (Hutchinson & Eardley, 2019). By crossing the borders of Translation Studies (TS) to gain insights from Museum Studies (MS), this paper claims that the ideal of achieving absolute objectivity is problematic and that a comparison between museum ADs and other tools for the visit would be a beneficial contribution to the objectivity vs. subjectivity debate. In light of current theories in MS, this study seeks to explore subjectivity in museum ADs (primarily addressed to visually impaired visitors) and general audio guides (AGs). Trailing previous research into subjectivity in museum ADs (Gallego, 2019), a text-focused analysis based on the appraisal theory (Martin & White, 2005) was conducted on a corpus of ADs and AGs to highlight discrepancies in terms of subjectivity between museum communicative practices aimed at different target audiences. Lay summary Audio description (AD) is a service addressing primarily blind and partially sighted people to provide them access to visual or audiovisual products, such as images, objects, places and films. Whether AD should describe something objectively is still an open and unresolved question, even more so when considering less researched types of AD, such as museum ADs, which describe specimens, artefacts, and artworks that are exhibited in museums. Few specific guidelines on how to describe artworks and cultural artefacts exist and tend to favour a neutral approach. However, no clear consensus exists, and some scholars have already highlighted the limits of a factual style. This paper claims that the ideal of achieving absolute objectivity in museum AD is problematic and that a comparison between museum ADs and other tools for the visit, such as general audio guides, would be a beneficial contribution to this debate. This study draws on research focusing both on audio description and museums and seeks to analyse subjectivity in museum ADs and general audio guides (AGs), which are similar texts describing museum objects for different target audiences (non-sighted and sighted visitors respectively). Trailing previous research into subjectivity in museum ADs, the analysis focuses on a collection of AD and AG texts. We have analysed them by adopting the appraisal theory to highlight differences between the two groups of texts.